Predictive tools for rangeland health, livestock feed security and rangeland restoration in the Horn of Africa - IGAD Centre for Pastoral Areas and Livestock Development (International Livestock Research Institute, 2025)
Video recordiing of the session at the IGAD Centre for Pastoral Areas and Livestock Development (ICPALD), the Jameel Observatory for Food Security Early Action and the Supporting Pastoralism and Agriculture in Recurrent and Protracted Crises (SPARC) Programme 'Building the Resilience and Prosperity of Pastoralists and Dryland Communities' research and policy dialogue in Nairobi on 1 and 2 October 2025.